Computational Modeling of Distinct Neocortical Oscillations Driven by Cell-Type Selective Optogenetic Drive: Separable Resonant Circuits Controlled by Low-Threshold Spiking and Fast-Spiking Interneurons - Vierling-Claassen, Dorea; Cardin, Jessica; Moore, Christopher I.; Jones, Stephanie R. (Frontiers in Human Neuroscience, 2010)
Selective optogenetic drive of fast spiking interneurons (FS) leads to enhanced local field potential (LFP) power across the traditional “gamma” frequency band (20-80Hz; Cardin et al., 2009). In contrast, drive to regular-spiking pyramidal cells (RS) enhances power at lower frequencies, with a peak at 8 Hz. The first result is consistent with previous computational studies emphasizing the role of FS and the time constant of GABAA synaptic inhibition in gamma rhythmicity. However, the same theoretical models do not typically predict low-frequency LFP enhancement with RS drive. To develop hypotheses as to how the same network can support these contrasting behaviors, we constructed a biophysically principled network model of primary somatosensory neocortex containing FS, RS and low-threshold-spiking (LTS) interneurons. Cells were modeled with detailed cell anatomy and physiology, multiple dendritic compartments, and included active somatic and dendritic ionic currents. Consistent with prior studies, the model demonstrated gamma resonance during FS drive, dependent on the time-constant of GABAA inhibition induced by synchronous FS activity. Lower frequency enhancement during RS drive was replicated only on inclusion of an inhibitory LTS population, whose activation was critically dependent on RS synchrony and evoked longer-lasting inhibition. Our results predict that differential recruitment of FS and LTS inhibitory populations is essential to the observed cortical dynamics and may provide a means for amplifying the natural expression of distinct oscillations in normal cortical processing.